Development of Non Formal Education in the Era of Free Learning - Susiana, Aprina; Setiawati, Setiawati (Universitas Negeri Padang, 2024)
The implementation of independent learning programs is expected to meet what students need, organize learning according to their interests and abilities, and build the character of students according to the values of Pancasila. Non-formal education is an educational path outside formal education that has the aim of continuing the acceleration of world development and meeting the needs of situations and circumstances, even in the current age of education. The independent learning policy was implemented by the Ministry of Education and Culture as an answer to the needs of the education system during the 4th century Revolution. The purpose of the research is to understand and know the development of non-formal education as a learning method for students at the age of independent learning and this research uses library research. Using information sources such as magazines, research reports, news, books, and so on. Within the framework of non-formal education, the role of the Mandiri Belajar Program is to develop the potential of learners from basic levels such as literacy and numeracy to advanced levels by implementing challenging programs aimed at providing the widest possible learning opportunities with freedom. Learn as much as possible, so that motivation arises in him through independent thinking, joy and no pressure to learn, so that in the framework of appropriate non-formal education, students have the skills, abilities and knowledge that are in accordance with their ideals and desires in the frame of Nonformal Education according to their needs.